Muamalah Fiqh Analysis of Murabahah - Mohammad Ghozali; Akhmad Novandi Nurtajuddin; Akmal Hibatullah Ramadhan (al-Afkar, Journal For Islamic Studies, 2025)
Murabahah as buying and selling where the owner of the goods mentions the purchase price of the goods, then takes advantage of the buyer by saying "I bought this item as a dinar and you give me a profit of one or two dinars. Or give details by saying: you give a profit of one dirham per one dinar or use a certain size even with a percentage. Hanafiyyah scholars define it as the transfer of something owned with an initial contract and an initial price accompanied by additional profits. According to Shafiyyah and Hanabilah scholars, Murabahah is buying and selling at the cost or acquisition price of goods from the seller plus a profit of one dirham for every ten dinars. Or something like that, with the condition that both parties to the transaction must know the cost price, while Ibn Rushd in bidayatul mujtahid gives a definition of Buying and Selling Goods at the original price at the agreed price.